2015
DOI: 10.1186/s13167-015-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind randomized placebo-controlled multicenter clinical trial (phase IIa) on diindolylmethane’s efficacy and safety in the treatment of CIN: implications for cervical cancer prevention

Abstract: BackgroundThe article presents the results of a clinical trial on the efficacy and safety of a novel pharmaceutical composition in the form of vaginal suppositories containing diindolylmethane in the course of cervical intraepithelial neoplasia (CIN) I–II conservative treatment. It offers an attractive drug therapy for more personalized prevention of cervical cancer.MethodsA total of 78 women of reproductive age were included. This was a multicenter, randomized, placebo-controlled, double-blind, parallel-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Due to the fact that no information is given concerning the distribution of CIN1 and CIN2, the groups are not comparable. Because of this lack of important information in this study a statement of the treatment efficacy is difficult [ 32 ]. Two other randomized controlled trials, however only for CIN2 and more ( +), showed significant treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that no information is given concerning the distribution of CIN1 and CIN2, the groups are not comparable. Because of this lack of important information in this study a statement of the treatment efficacy is difficult [ 32 ]. Two other randomized controlled trials, however only for CIN2 and more ( +), showed significant treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, 78 patients aged 18–39, with CIN1/2 from 90 to 180 days, received a medication depending on the improvement. The rate of CIN regression, based on histology, was 100% in the 200‐mg dose group, 95% at a dose of 100 mg, and 61% in the placebo group (Ashrafian et al, ). Although complete response in our study was 52%, but the time for intervention was also lower (3 months against 6 months).…”
Section: Discussionmentioning
confidence: 99%
“…In the group of women receiving DIM at a dose of 200 mg/day and 100 mg/day, a 100% (CI 95% = 82.35–100.00%) and 90.5% (CI 95% = 69.62–98.83%) regression of CIN lesions on histological examination were observed, respectively. However, in the placebo group, only 61.1% of the patients had a regression of the lesions on histological examination (CI 95% = 35.75–82.70%) [ 129 ]. The presented results indicate a significant potential of I3C and its DIM derivative in the chemoprevention of cervical cancer.…”
Section: Phytochemicals In Cervical Cancer Preventionmentioning
confidence: 99%